Answer:
11.18 miles
Step-by-step explanation:
The sides of a right triangle a, b, c are related by the equation
a^2 + b^2 = c^2
where c is the longest side of the triangle
Hence given that A connects B and C directly and forms a right angle at A
5^2 + 10^2 = c^2
Where c is the length of the road
25 + 100 = c^2
125 = c^2
c = 125^1/2
= 11.18 miles
Answer:
The other endpoint is (-33, 17)
Step-by-step explanation:
The rule of the mid-point of a segment whose endpoints are
(
,
) and (
,
) is
In our question
∵ The coordinates of the endpoints of a segment are (-15, 13) and (x, y)
∴
= -15 and
= x
∴
= 13 and
= y
∵ The coordinates of the mid-point of this segment are (-24, 15)
∴
= -24 and
= 15
→ Use the rule of the mid-point to find x and y
∵ ![-24=\frac{-15+x}{2}](https://tex.z-dn.net/?f=-24%3D%5Cfrac%7B-15%2Bx%7D%7B2%7D)
→ Multiply both sides by 2
∴ -48 = -15 + x
→ Add 15 to both sides
∴ -33 = x
∵ ![15=\frac{13+y}{2}](https://tex.z-dn.net/?f=15%3D%5Cfrac%7B13%2By%7D%7B2%7D)
→ Multiply both sides by 2
∴ 30 = 13 + y
→ Subtract 13 from both sides
∴ 17 = y
∴ The other endpoint is (-33, 17)
44 is your anwser
hope you do great !!!!!!!!!!
Answer:
-2
Step-by-step explanation:
Remember to follow PEMDAS. First solve parenthesis, power, multiplication, then add.
(5 - 2) = 3
(-4)² = (-4)(-4) = 16
3(-6) = -18
16 + (-18) = 16 - 18 = -2
-2 is your answer.
~
Answer:
x = 0, y = 1
Step-by-step explanation:
2x + 6y = 6 → (1)
x - 3y = - 3 ( add 3y to both sides )
x = 3y - 3 → (2)
substitute x = 3y - 3 into (1)
2(3y - 3) + 6y = 6 ← distribute parenthesis and simplify left side
6y - 6 + 6y = 6
12y - 6 = 6 ( add 6 to both sides )
12y = 12 ( divide both sides by 12 )
y = 1
substitute y = 1 into (2)
x = 3(1) - 3 = 3 - 3 = 0
solution is x = 0 , y = 1